Peran Vitamin D pada Psoriasis: Tinjauan Pustaka - Az-zuhra Irmi Putri; Yenni Yenni; Sofa Inayatullah (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Psoriasis is a chronic inflammatory skin disease characterized by keratinocyte hyperproliferation, inflammation, and neoangiogenesis, largely driven by dominant T helper 1 (Th1) and T helper 17 (Th17) immune responses. Psoriasis is associated with metabolic, psychological, cardiovascular, and arthritic comorbidities. Vitamin D plays an important role in the management of psoriasis. Calcitriol (1,25(OH)₂D₃), regulates keratinocyte proliferation, differentiation, and apoptosis. Vitamin D supports the formation of the cornified envelope as well as epidermal lipid and ceramide production, also acts synergistically with the epidermal calcium gradient to maintain barrier function. In addition to its epidermal effects, vitamin D exerts immunomodulatory actions by enhancing regulatory T cells and anti-inflammatory cytokines (interleukin (IL)-10, IL-4, transforming growth factor-beta (TGF-β)), while suppressing Th1/Th17 activity and production of pro-inflammatory cytokines (IL-2, IL-17, tumor necrosis factor-alpha (TNF-α)). These mechanisms highlight its potential role in psoriasis therapy. Topical vitamin D₃ analogues are effective for mild to moderate disease due to the high expression of vitamin D receptors in psoriatic keratinocytes. Oral supplementation has also been explored for its systemic immunomodulatory effects, although findings remain inconsistent.